Inter-carrier interconnection services: QoS, economics and business issues - Courcoubetis, C.; Dramitinos, M.; Stamoulis, G. D.; Blocq, G.; Miron, A.; Orda, A. (2011 IEEE Symposium on Computers and Communications (ISCC), 2011)
The Internet has evolved towards a unique technology base for creating value-added services with worldwide connectivity. These services, enabled by the increasing bandwidth of access networks, result in new high-performance applications (e.g. e-health, high definition video streaming, network gaming etc.) To support and materialize the value of these emerging services, it is important for the operators to be able to provide some form of Quality of Service (QoS) assurance. This paper presents the main economic issues regarding the efficient provisioning of such services in inter-domain level and overviews some candidate economic mechanisms and game-theoretic tools that could be adopted.